About the POD application for separating acoustic and turbulent fluctuations from wall pressure synthesised field. (1st January 2014) - Gaudard, Eric; Druault, Philippe; Marchiano, Régis; Van Herpe, François
A turbulent flow developing over rigid surface generates two types of excitation loadings: a turbulent flow component that directly impacts the plate and an acoustic component that originates in turbulent flow. The analysis of these loadings is of particular interest especially for future noise reduction strategy implementation in an automobile context. To reproduce acoustic and turbulent fields, a synthesis of random pressure field is proposed thanks to Corcos's model and a diffuse acoustic field. One then proposes to evaluate the ability of proper orthogonal decomposition to discriminate both parts of this synthesised field. Such POD application demonstrates that it acts as a filtering technique in the wavenumber space. But in present study, the acoustic component is shared by multiple POD modes, and therefore cannot be extracted directly. It is also emphasised that such application depends on the frequency resolution and the energy repartition of the synthesised field.